Flat sheet membrane composite for desalinisation applications based on Bacterial Nanocellulose (BNC) from banana peel waste, cellulose, and silica - Edwin K Sijabat; Ahmad Nuruddin; Pingkan Aditiawati; Bambang Sunendar Purwasasmita (Materials Research Express, 2020)
This research reports the making of flat sheet membrane composite for desalination applications based on Bacterial Nanocellulose (BNC) from banana peel waste, wood cellulose, and silica. Silica synthesized using the sol-gel method resulted in particles range 189–227 nm in size. Characterization with FTIR further confirms the silica cluster produced from the synthesis. The membrane was successfully made in the form of flexible paper sheets in three compositions: T1 (BNC 60%, microcellulose 20%, and silica 20%), T2 (BNC 50%, micro cellulose 20%, and silica 30%), and T3 (BNC 40%, microcellulose 20%, and silica 40%). The SEM characterization shows the constituent elements, BNC, microcellulose, and silica, were evenly spread on the resulting flexible membrane sheet and shows matrix of BNC and micro cellulose while the space between them are filled in by silica particles. EDS characterization are carried out to observe morphology and dominant element on the membrane. Performance test of the membrane was done at pressure 4 bar. The T3 membrane had the largest maximum flux value of 4.412 × 10 ^3 l m ^−2 h. The T2 membrane had the highest salt rejection value of 4.89% in the first minute, but the value was lower than T1 at the end of five minutes. The salt flux and rejection values of the entire membrane tend to decrease with time due to clogging on the membrane surface.